2018
DOI: 10.1007/s13205-018-1117-2
|View full text |Cite
|
Sign up to set email alerts
|

β-Ecdysterone accumulation and regulation in Ajuga multiflora Bunge suspension culture

Abstract: Bunge cells contain β-ecdysterone (β-EC) that regulates the molting process of insect larvae. In this study, different conditions of culture have been studied to optimize the production of β-EC. Bunge growth fitted the curve of logistic equation with one growth cycle of 17 days. The electric conductivity of medium had a negative correlation with not only the weight of dry cell but also the β-EC accumulation, and thus, could be used for monitoring the peak of both cell growth and β-EC accumulation. The pH value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Treatment with 0.15 mg/l ABA of A. lobata suspension cultures could promote 20E content increase in the short term but was not suitable for long-term culture, and browning was observed. In Wang et al (2018) study, the browning also happened, which might be caused by the toxicity of ABA. In recent years, studies have shown that ABA can regulate and stimulate the production of secondary metabolites such as chlorogenic acid, phenols, flavonoids and terpenoid substances (Sandhu et al 2011;Buran et al 2012).…”
Section: Discussionmentioning
confidence: 86%
“…Treatment with 0.15 mg/l ABA of A. lobata suspension cultures could promote 20E content increase in the short term but was not suitable for long-term culture, and browning was observed. In Wang et al (2018) study, the browning also happened, which might be caused by the toxicity of ABA. In recent years, studies have shown that ABA can regulate and stimulate the production of secondary metabolites such as chlorogenic acid, phenols, flavonoids and terpenoid substances (Sandhu et al 2011;Buran et al 2012).…”
Section: Discussionmentioning
confidence: 86%
“…Dicha ubiquidad supuso la base de investigación para la búsqueda de moléculas similares fuera del metaboloma de artrópodos. Análogos a ecdiesteroides han sido descubiertos en diferentes géneros de plantas, denominándose fitoecdiesteroides (PE, de sus siglas en inglés, Phytoecdyteroids) (4,5) . Su función principal permanece aún refutable.…”
Section: Introductionunclassified